Statistical Analysis of Foreign Investments in the Republic of Macedonia 2010-2016 - /, Shpresa Syla (Advances in Social Sciences Research Journal, 2018)
The aim of this paper is to examine the impact of foreign direct investments (FDI) on the economic growth and the reduction of unemployment, following an empirical research for the Republic of Macedonia. Moreover, the paper investigates the transfer of know-how technology, workforce improvement, integration into the world economy, enhancing the competition in the country’s development and the reorganization of domestic firms and difficulties in implementing economic policies. The theoretical and empirical literature suggests dividing opinions and conclusions on the impact of FDI on the economic growth, unemployment and exports. In order to fully understand the flow of FDI in the economic growth through transition countries and their potential economic growth, unemployment and export relations, we have prepared descriptive analyzes, elaborated by charts and tables. In this paper, we have developed empirical models for the Repbulic of Macedonia, a model of FDI impact on the economic growth and unemployment. The analysis uses data from 2012-2017. For the purpose of solving the patterns, the following techniques have been used: broken graphics and regression with the OLS method. The foremost conclusion is to show the relationship between FDI and the economic growth, as well as the relationship between FDI and unemployment in the Republic of Macedonia and FDI relations. Further recommendations will be addressed which aim to improve the country’s economic position in attracting foreign investors. Key words: gdp, unemloymend, fdi, export, regression